Analisis Dampak Penambangan Emas Terhadap Kondisi Lingkungan Dalam Tinjauan Ekonomi Islam - Muhammad Alhadi Mustopa; Nurida Isnaeni (Universitas Batanghari Jambi, 2026)
Gold mining activities play an important role in improving the economic conditions of both communities and the state. However, these activities often cause negative environmental impacts, such as water and soil pollution, ecosystem degradation, and a decline in the quality of life of communities living around mining areas. This study aims to examine the environmental impacts of gold mining from the perspective of Islamic economics. The research method employed is a literature review by analyzing various sources that discuss gold mining, environmental issues, and the concepts of Islamic economics. The results indicate that gold mining practices that neglect environmental sustainability are not in accordance with the principles of Islamic economics, particularly the values of trust (amanah), justice, and public welfare (maslahah). From the perspective of Islamic economics, natural resources are considered a trust that must be managed wisely and sustainably. Therefore, gold mining activities are only acceptable when they are carried out by applying environmentally friendly principles, responsible waste management, and fair policies for local communities and the surrounding environment. This study emphasizes the importance of balancing economic benefits with environmental conservation in order to achieve sustainable welfare.